2018
DOI: 10.1038/s41419-018-1090-z
|View full text |Cite|
|
Sign up to set email alerts
|

Long noncoding RNA neuroblastoma-associated transcript 1 gene inhibits malignant cellular phenotypes of bladder cancer through miR-21/SOCS6 axis

Abstract: Bladder cancer (BC) is one of the most common tumors in the urinary system. Noncoding RNAs are considered to take part in cellular phenotypes and are emerging as diagnostic and prognostic biomarkers of BC. The aim of this study is to investigate the clinical significance of neuroblastoma- associated transcript 1 (NBAT1) gene and its effects on malignant cellular phenotypes in BC. NBAT1 gene was low-expressed in BC tissues and cell lines and its low-expression was related with high pathological grade and metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…SOCS6 is a member of SOCS family proteins that are known as regulators of inflammatory responses induced by bacterial infections [34]. Also, SOCS6 is identified as a cytokine-inducible negative regulator of cytokine signalling [35] and is involved in negative regulation of receptor signalling and inducing apoptosis by targeting mitochondrial proteins [36]. Evidence also points out that SOCS6 is implicated in diverse human cancers [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…SOCS6 is a member of SOCS family proteins that are known as regulators of inflammatory responses induced by bacterial infections [34]. Also, SOCS6 is identified as a cytokine-inducible negative regulator of cytokine signalling [35] and is involved in negative regulation of receptor signalling and inducing apoptosis by targeting mitochondrial proteins [36]. Evidence also points out that SOCS6 is implicated in diverse human cancers [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are hotspots in current research, in which anomalous expression of certain lncRNAs is found in a variety of malignant cancers, and those lncRNAs can act as tumor-suppressing genes or oncogenes to play a part in genesis and progression of tumors [12,13]. It is well known that ln-cRNAs possess various functions and are involved in almost all cancer cell characteristics, including apoptosis, invasion, autophagy and chemotherapy resistance [14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA neuroblastoma associated transcript 1 (NBAT1), also known as CASC14, was located at 6p22.3 and was initially identified to be dysregulated in neuroblastoma 16 . Then, several studies reported that NBAT1 expression was down-regulated in several tumors, such as bladder cancer, glioblastoma, osteosarcoma [17][18][19] . In addition, both in vitro and in vivo assays confirmed the tumor-suppressive roles of NBAT1 in the above tumors.…”
Section: Rna Preparation and Quantitative Rt-pcrmentioning
confidence: 99%